Correction: The importance of phase equilibrium for doping efficiency: iodine doped PbTe. Issue 2 (25th January 2022) - Male, James; Agne, Matthias T.; Goyal, Anuj; Anand, Shashwat; Witting, Ian T.; Stevanović, Vladan; Snyder, G. Jeffrey
Abstract : Correction for 'The importance of phase equilibrium for doping efficiency: iodine doped PbTe' by James Male et al., Mater. Horiz., 2019, 6, 1444–1453, DOI: ; 10.1039/C9MH00294D .